EFEKTIVITAS PELAKSANAAN PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) DI KECAMATAN BUNGARAYA KABUPATEN SIAK - Nursyaifuloh "; Endang Sulistyaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The rural agribusiness development program (PUAP). Is a program creaded by the central government to empower rural communities to tackle the program of poerty. National program in direct contact with the community in order to assist and improve the wotfare and needs of life This research aims to know about the effectiveness of the implementation of rural agribusiness development program (PUAP), and the faktors that the effectiveness of the implementation of rural agribusiness development program (PUAP) in the district Bungaraya Siak district. This study descriptive qualitative data collection techniguen of observation, interviews, and research informants were determined by purposive sampling technique The results of a descriptive qualitative data analysis found that the efectiveness of the implementation of rural agribusiness development program (PUAP) in the district Bungaraya, it can be seen from, the achievement of objectives and the expected rate of change in the national proram is not target funds PUAP progrram, the neffec tiveness of the a mount of unds granted and the settlement of funds in arrears. In this research note the factors that influence the effectiveness of the implementation of rural agribusiness development program (PUAP) in the district Bungaraya, include organizational factors that are still not ging well, the factor implementing inadequate in terms of quality and quantity. Keywords : Effectiveness, PUAP program